Peruvian Medical Education at the Beginning of the Third Millennium. Introduction - Piscoya Arbañil, José (1998)
The Peruvian University, referring to the University and not genuine centers where higher education recently formed with mercantilist or proselytizing purposes is taught, remains a space for reflection, an institution located within a given historical reality that not only serves base, but is a temporal and spatial situation that must be studied, analysis, evaluation and judgment.